2018
DOI: 10.1080/09637486.2018.1446916
|View full text |Cite
|
Sign up to set email alerts
|

BioPepDB: an integrated data platform for food-derived bioactive peptides

Abstract: Food-derived bioactive peptides play critical roles in regulating most biological processes and have considerable biological, medical and industrial importance. However, a large number of active peptides data, including sequence, function, source, commercial product information, references and other information are poorly integrated. BioPepDB is a searchable database of food-derived bioactive peptides and their related articles, including more than four thousand bioactive peptide entries. Moreover, BioPepDB pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Moreover, the investigations of determination of biologically active activities of peptides sequences might be performed in silico in accordance with the procedure provided in the created data bases that might be designed to analyze a wide range of biopeptides and their precursors or to determination-selected sources of proteins, e.g., milk bioactive peptide database [30-33, 40, 41]. The identification and analysis of peptide bioactivity presented in this article are also applied in the interdisciplinary research [30][31][32][33][40][41][42]. The findings have revealed that diverse biopeptides can be also obtained through the hydrolysis of α-la and CGMP conducted with using selected L. helveticus strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the investigations of determination of biologically active activities of peptides sequences might be performed in silico in accordance with the procedure provided in the created data bases that might be designed to analyze a wide range of biopeptides and their precursors or to determination-selected sources of proteins, e.g., milk bioactive peptide database [30-33, 40, 41]. The identification and analysis of peptide bioactivity presented in this article are also applied in the interdisciplinary research [30][31][32][33][40][41][42]. The findings have revealed that diverse biopeptides can be also obtained through the hydrolysis of α-la and CGMP conducted with using selected L. helveticus strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Peptides in BioDADPep are compared with peptides in IEDB (Immune Epitope Database) [11] to extract antidiabetic peptides with cross reactivity features with anticancer, anti-inflammatory, anti-microbial, antioxidant, autoimmune and allergic. Such peptides in databases like THPdb [12], ADP3 [13]; LAMP [14]; AHTPDB [15]; AVPdb [16];BioPepDB [17]; CancerPPD [18]; CPPsite [19]; DRAMP 2.0 [20]; SATPdb [21]; HIPdb [22]; CAMPR3 [23] and MBPDB [24] are also used for enrichment of the database.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, peptide definition has come into a debate, with the Food and Drug Administration defining a peptide as any polymer composed of 40 or fewer amino acids [16] and the European Medicines Agency considering them as small molecules if created chemically or as biological entities if extracted from natural sources [17]. Thus, their classification remains contested [18]. Here, peptides were considered molecules consisting of amino acids linked by peptide bonds, ranging from 2 to 50 residues [19].…”
Section: Properties Of Therapeutic Anticancer Peptidesmentioning
confidence: 99%